Analyzing the factors that can limit the acceptability to introduce new specializations in higher education institutions: A case study of higher education institutions of Southern Punjab, Pakistan. Issue 4 (8th May 2017) - Abbas, Wasim; Ahmed, Munir; Khalid, Rizwan; Yasmeen, Tehreem
Abstract : Purpose: The purpose of this paper is to provide a comprehensive view of barriers that restrict the adoption of new specializations and courses in the higher education institutions of Southern Punjab, Pakistan. Design/methodology/approach: Quantitative methods were used to get the responses from the respondents of different institution of target areas. Results were further analyzed with the help of statistical tools. In total, 203 respondents were approached to fill the carefully designed questionnaire. Findings: Results of the study clearly show four major factors, including internal barrier, external barrier, cultural barrier and leadership barrier, that are restricting the introduction and adoption of new specialization courses in higher education institutes of Southern Punjab. Suggestions at the end are made to address the restrictions. Research limitations/implications: The current study states only six higher education institution of Southern Punjab, which is a kind of limitation itself. This study is conducted by taking into account the needs and trends of the businesses and markets; student perspective is not taken about the situation in this study, which is an another limitation of the study. To get more accurate and validated results, the higher education institutions located in other areas of Pakistan could be studied, which was not done in this study because of time and resource limitations. Practical implications: This study may prove worthy to bring a positive and practical shift in the Pakistani higher education system. This study may also prove beneficial to show the actual picture of the situation to national leaders, academician and policy maker so that things are taken seriously to actually align the Pakistani higher education system with the emerging market demands and trends. Suggestions made in this study may provide comprehensive guidelines to the academic strategists to uplift the higher education institutions of Pakistan up to the international standards and requirements, so the Pakistani higher education institutions can get a respectful place in the international academic rankings. Originality/value: The paper highlights the restrictions and helps the institutions to introduce new specialization courses.